Micro Enterprise Strategy for Economic Independence in Islamic Boarding Schools - Helfiana, Afrilia; Maadi, Alan Su’ud (Indonesian Journal of Law and Economics Review, 2025)
General Background: Islamic boarding schools (pesantren) play a strategic role not only in religious and cultural education but also in community-based socio-economic empowerment. Specific Background: Growing economic challenges and dependence on external funding have driven pesantren to establish micro-enterprise units as instruments of institutional independence. Knowledge Gap: However, limited market reach, restricted capital access, and inadequate managerial competence continue to hinder the optimization of pesantren-based micro businesses. Aims: This study analyzes the economic development strategy of the Syaichona Moh Cholil Islamic Boarding School Bangkalan through the management of integrated micro-enterprise units. Results: Findings show that the pesantren has successfully strengthened economic resilience through diversified micro businesses—such as Podea sandal production, ADEM bottled water, cooperatives, retail shops, and service units—managed professionally by students and alumni using sharia principles and supported by digital technology integration. Novelty: This research highlights a unique model of pesantren economic governance that combines business diversification, internal human-resource mobilization, inter-pesantren collaboration, and cashless digital ecosystems linked to student financial monitoring. Implications: The study affirms that micro-enterprise development enhances institutional independence, cultivates entrepreneurial competence among students, and supports broader community economic empowerment. Highlights: The pesantren strengthens economic independence through diversified micro-enterprises managed by students and alumni. Sharia-based business governance and digital financial systems improve transparency and efficiency. Micro-business development enhances entrepreneurial skills and community economic empowerment. Keywords: Pesantren Economy, Micro Enterprises, Economic Independence, Sharia Based Management, Digital Transformation